The relationship between the perceived movement quality and the kinematic pattern of complex skills in gymnastics - Mack, M.; Schmidt, M.; Heinen, T. (Journal of Human Kinetics, 2021)
The study aimed to investigate the relationship between the perceived movement quality of a gymnastics skill and its kinematic pattern, as well as the influence of expertise. Thirty participants with different levels of gymnastics expertise (n = 10 visual experts, n = 10 motor experts and n = 10 novices) were recruited for the study. They were instructed to compare the movement quality of eleven video sequences, showing different handstand - back handspring performances. To extract the kinematics, the performances were digitized. By means of an ongoing cluster analysis, the kinematic pattern as well as the pattern of the perceived movement quality of the skills were determined for each experimental group. The results of the cluster analysis of the different experimental groups were analyzed and compared. Expertise differences were found regarding the pattern of the perceived movement quality. There was a significant correlation between the dendrograms of the visual experts and the motor experts (p = .021), as well as between the dendrograms of the visual experts and the novices (p = .011). There was no significant correlation between the dendrograms of the motor experts and the novices (p = .173). The pattern of the perceived movement quality was not correlated with the holistic kinematic pattern of judged skills (p > .143). These results suggest perceptual and cognitive differences of the participants due to their different previous visual and motor experience.